PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA SMP UNTUK MENGONSTRUKSI VOLUME BANGUN RUANG - Syofni (Jurnal Prinsip Pendidikan Matematika, 2019)
This research is the development research, which aims to develop a formula for constructing props volume beams and tubes that can be used in primary and secondary education levels. This research has resulted 1) A set of props to construct formulas accompanied beam volume usage procedures, 2) A set of props to construct the volume of the tube with the procedures used. The process begins with the development of props issue of lack of teachers ability (participants PLPG 2013) to describes the process of formation of the volume formula beams and tube, then researchers design and make the props, then performed the validation and testing. The results of the validation state that props valid for use in primary and secondary education level.